2(m-5)+6=2m-4

Simple and best practice solution for 2(m-5)+6=2m-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m-5)+6=2m-4 equation:


Simplifying
2(m + -5) + 6 = 2m + -4

Reorder the terms:
2(-5 + m) + 6 = 2m + -4
(-5 * 2 + m * 2) + 6 = 2m + -4
(-10 + 2m) + 6 = 2m + -4

Reorder the terms:
-10 + 6 + 2m = 2m + -4

Combine like terms: -10 + 6 = -4
-4 + 2m = 2m + -4

Reorder the terms:
-4 + 2m = -4 + 2m

Add '4' to each side of the equation.
-4 + 4 + 2m = -4 + 4 + 2m

Combine like terms: -4 + 4 = 0
0 + 2m = -4 + 4 + 2m
2m = -4 + 4 + 2m

Combine like terms: -4 + 4 = 0
2m = 0 + 2m
2m = 2m

Add '-2m' to each side of the equation.
2m + -2m = 2m + -2m

Combine like terms: 2m + -2m = 0
0 = 2m + -2m

Combine like terms: 2m + -2m = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 7r+6=62 | | 5(x+3)+12x=4-7(2-x) | | 2(m-5)+6=2m+22 | | x-0.25x=95 | | X^3+28X^2=0 | | x+3-2x=5 | | 2(m-5)+6=2m-1 | | x^2=392 | | -3x-4y(3x+3y)=-1 | | x^2+y^2=784 | | -3x-9=-75+3x | | 2(m-5)+6= | | 1-5x=10-2x | | -6=3(u+-3) | | 15x+6=2x-3 | | 3x+7=6x+7 | | 4(n-3)-2(-3+n)= | | -3(-5u+6)-3u=4(u-6)-8 | | 10+4y= | | 8(4x-1)-12x=(2x-6) | | n(2)+14=98 | | n(2)14=98 | | -1/2x+3(0)=-3 | | 2log(2x)=1 | | -6=3-m | | 125n^2-45=0 | | 0.04x+0.03(x-20)=1.25 | | 6x-61=-3x+65 | | 4(w+1)+4=20 | | 5x-3=6x-7 | | -3e+2=5e-4 | | 3-.75x=8 |

Equations solver categories